O uso da inteligência artificial, modelagem matemática e resolução de problemas como potencializadores no processo de ensino e aprendizagem de matemática no sétimo ano do ensino fundamental - Yassaki Filho, Julius Kahoru (2024)
The primary objective of this research is to verify the potential of using Artificial Intelligence, Mathematical Modeling and Problem Solving in the 7th grade of Elementary School. The motivation for this work stemmed from the fact that new technologies frequently emerge, yet schools often fail to absorb these new developments, sometimes even resisting their use. Given that Artificial Intelligence is currently a major topic, heralded by some as the greatest cognitive revolution in our history, it is considered highly important to examine the possibilities of this tool within the educational environment, and specifically in this research, in the learning of Mathematics. For this purpose, a didactic sequence was developed, beginning with the introduction of technological tools to the students, followed by presenting some problems to be solved, climatic situations that can be modeled and their modeling, the mathematical theory used, and the presentation of results. The activity was conducted with a group of five 7th-grade of Elementary School students from a public school in the metropolitan region of Porto Alegre. The choice of students at this educational level is due to the fact that Algebra content is introd uced at this stage, marking a significant conceptual and mathematical abstraction paradigm shift. This skill is a substantial challenge for the current generation, known as Generation Alpha, which is driven by agility, curiosity, independence, difficulty concentrating, surrounded by technology and connectivity, and values experience over theory. On the other hand, AI might cause students not to exert effort in solving the proposed exercises, thus hindering their learning. The research resulted in some relevant findings about the use of this tool: it encourages student engagement in Math classes, aids in the individualization of teaching, supports the transition from concrete operational to formal operational stages according to Piaget's genetic epistemology. The use in Math classes must be supervised and all results validated, as Artificial Intelligence can make errors, and ultimately, it can cause cognitive dependence if used improperly and without teacher supervision.